Hubungan Faktor Demografi, Klinik dan Hasil Luaran Pada Ibu Bersalin Dengan PreekIamsia/Eklamsia - Retno Dumilah; . Sukriani; FF Wirakusumah (Poltekkes Kemenkes Bandung, 2013)
Preeclampsia and eclampsia remains become the leading causes of matemal mortality in obstetrics. Many studies showed that the occurence of preeclampsia and eclampsia are influenced by demographic and clinical factors that affectmaternal and infant outcome. The purpose of this study was to determine the correlation between demographic factors (including age, parity, and education), clinical (history of preeclampsia in the mother's family) and the outcomes of maternal and infant in mothers with preeclampsia/eclampsia in the department. Dr. Hasan Sadikin General Hospital 20112012. Cross sectional research was conducted in March to April 2013. The source of the data was Maternal Care Monitoring Card of parturient with hypertension in the period of January 1, 2011 until December 31, 2012. Data was divided into 2 groups which were preeclampsia/eclampsia group (122 data) and other hypertensive disorders in pregnancy group which includes gestational hypertension, chronic hypertension and superimposed preeclampsia (168 data). Statistical analysis was performed with Chi square test and logistic regression.Bivariate analysis results showed that there were significant differences between age, parity, type of delivery and preterm birth on preeclampsia/eclampsiagroup compared to other hypertensive disorders in pregnancy group (p<0,05), but there was no significant difference between variables of education and preeclampsia history in mother's family with preeclampsia/eclampsia group compared to other hypertensive disorders in pregnancy group (p>0,05). Multivariable analysis results indicated that there was significant correlation between primiparous, extraction forceps delivery, sectio cesarean and preterm birth with preeclampsia/eclampsia (p<0,05).Conclusions: there are a correlation between demographic factors and the outcomes on delivery mothers with preeclampsia/eclampsia in Dr. Hasan Sadikin General Hospital in 2011-2012. Midwives need to improve the ability to make early detection, early treatment and referral for patients with preeclampsia/eclampsia.